History and truth in Ignacio Ellacuría: Contributions for a philosophical reflection on Central America - Carrera Umaña, Randall (2025)
This research develops the thesis that history and truth are fundamental categories of Ignacio Ellacuría's philosophy, although they are taken from his teacher Xavier Zubiri, they receive in Ellacuría an original approach. For both historical reality and truth conceived as a task orient his mature philosophy towards the analysis of the situation of the impoverished majorities of Central America. In order to understand its importance, we start by explaining the link between human reality and sentient intelligence, to later analyze the conception of history as appropriation and training, and truth as a task. Then, we move on to the study of its application to the Central American reality. Methodologically, an interpretive analysis of Ellacuría's texts has been chosen, using references to specialists only to expand and deepen some fundamental ideas. The research concludes that for a correct interpretation of Ellacuría's thinking on Central America, it is necessary to have a thorough understanding of his reflections on truth and history.